PENERAPAN METODE TIME OUT PADA ANAK KELOMPOK A TAMAN KANAK-KANAK ISLAM SEMESTA KHATULISTIWA - Darma, Cici; Marmawi, Marmawi; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to describe the application of the Time Out Method in group A children in the Equatorial Islamic Kindergarten. The Time Out method in question is to stop children aged 3-5 years from the activities they are doing. Usually the child will sit in a predetermined special place where 3-5 years old children may not leave the place before the specified time is up. The goal is to make children calmer, so that we as parents or caregivers are easier to talk to. Time Out's punishment has a good effect on children. Of the 11 research objects, the researcher focused the research on 1 (one) child who often received time out from the teacher due to the child's behavior. Data collection tools used by researchers are Observation Guidelines, Interview Guidelines, Archives or Documents, and Field Records. Data analysis in this study uses Qualitative Data Analysis. The results of the study are presented in the form of document attachments in the form of interviews with the Principal and Teachers of the Semsta Khatulistiwa Islamic Kindergarten and photos that are evidence in the study. The results showed that giving children time out provided learning for children to self-reflect in controlling emotions.Keywords: Time Out Method